Soil Carbon Storage in Douglas‐Fir Forests of Western Oregon and Washington Before and After Modern Timber Harvesting Practices. (4th April 2019) - Holub, Scott M.; Hatten, Jeff A.
Abstract : Core Ideas: Nine forest stands in the Pacific Northwest were selected to detect at least a 5% change in mineral soil carbon. Change in mineral soil carbon content following harvest was negligible (+2% ns). There was an increase of 184% in forest floor carbon resulting from harvest residue inputs. Conventional methods of timber harvesting do not cause substantial short‐term loss in mineral soil carbon. Forest soil carbon represents a large, but slowly changing pool of carbon in forests. Understanding the response of soil carbon to forest management, including harvesting, is critical for determining overall stand and/or landscape carbon balance. This longitudinal study on nine randomly selected sites was designed to detect a 5% or greater change in mineral soil carbon storage following harvest. Soil samples were collected both pre‐harvest and 3 to 3.5 yr post‐harvest at 300 sample points on a fixed grid from each stand. A forest floor sample and mineral soil samples in depth increments of 0 to 15 and 15 to 30 cm were collected at every point. A soil sample at 30 to 100 cm (or 30–60 cm at two sites) was collected at 200 points. Each mineral soil depth fraction was separated into size fractions of <2 mm and 2 to 4.75 mm for analysis. At each site, these samples were spatially grouped into 25 composites by depth and size for the efficient analysis of carbon concentration. Soil mass and carbon concentrations were multiplied to calculate the carbon content in the soil per unit area. Across all sites combined, we found negligible change (+2% ns) in mineral soil carbon content following harvest and a 184% increase in forest floor carbon resulting from harvest residue inputs. This indicates that conventional timber harvesting methods in the Pacific Northwest do not cause substantial short‐term losses in mineral soil carbon, but the longer‐term trajectory of soil carbon storage following harvest remains to be investigated.